Strategizing : new thinking about strategy, planning, and management - Bolland, Eric J. (Emerald Publishing, 2020)
Strategy is an essential part of business, but strategizing often gets ignored or left behind. In this exciting new work, Eric J. Bolland introduces strategizing as a key component of strategy development and execution, showing strategizing as a way to aid organizations with their futures.